Pengarauh Kebijakan Deviden Kebijakan Hutang dan Profitabilitas terhadap Ukuran Perusahaan Sektor dagang yang Terdaftar di Bursa Efek Indonesia - Irwan Taufik Marpaung; Ramadona Simbolon; Shofwan Andri; Sri Elviani (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2022)
Study aims to provide empirical evidence regarding dividend policy, policy, and profitability in predicting firm value by testing each ble. using the rupiah currency unit in financial reporting, the company not experience a loss.The method used in the selection of objects in this is purposive sampling involving 13 manufacturing companies listed on donesia Stock Exchange (IDX) for the 2017-2021 periode with an vation period of 5 (five) years with 65 samples of companies. The tical model used in this study is a multiple linear regression analysis which was carried out with the help of the SPSS version 26 for window am.The results of this study indicate that the Dividend Policy (DPR) rofitability (ROE) have a significant effect on firm value. while the debt (DER) does not show a significant effect on firm value.